The Powerful and Vulnerable Intercultural Encounters of Jesus - Hertig, Paul (Mission studies, 2015)
In this reading of the New Testament record, Jesus approached intercultural situations with wisdom, grace, and sensitivity. He interacted with Gentiles, marveled at their faith, and even sent them as missionaries to their own people. He followed cultural patterns when they were helpful; he resisted cultural patterns when they were hurtful. He often interacted with people whom even his disciples wanted to avoid. Through humility and vulnerability, he created an atmosphere that elicits transparency and transformation. Jesus walked along borderlands and traversed across borders into Gentile regions. In doing so, he engaged in intense theological discussions with a Canaanite woman and a Samaritan woman, and, in both cases, met them in their brokenness and met their deepest needs. At times he interacted with high people of society, for instance, the centurion. Prior to healing his servant, Jesus marveled at the centurion’s faith, declaring it greater than all of Israel.